ASME 2009 InterPACK Conference, Volume 2 2009
DOI: 10.1115/interpack2009-89340
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Double Walled Telecommunication Cabinet on Solar Load: Natural and Forced Convection

Abstract: Access networks provide the last mile of connectivity to telecommunications customers throughout the world. Voice, data, and video services through fiber, copper, and wireless media are all delivered to the end user by the access portion of the network. In an access network, thermal management of active electronics and optical devices is critical to network reliability and performance. In these networks, outside plant telecom enclosures provide environmental protection for both active electronics and optical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mariam et al [1] studied the effects of door fan design on the thermal properties of telecommunications cabinets. Muralidharan et al [2] examined the advantages of double-walled cabinet design over single-walled with respect to solar loading. They found that the extra layer of wall material greatly improved the solar protection to the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mariam et al [1] studied the effects of door fan design on the thermal properties of telecommunications cabinets. Muralidharan et al [2] examined the advantages of double-walled cabinet design over single-walled with respect to solar loading. They found that the extra layer of wall material greatly improved the solar protection to the system.…”
Section: Literature Reviewmentioning
confidence: 99%